Unravelling the Mystery: Enlightenment of the Uncommon Electrochemistry of Naphthalene Monoimide [FeFe] Hydrogenase Mimics - Benndorf, Stefan; Hofmeister, Elisabeth; Waechtler, Maria; Goerls, Helmar; Liebing, Phil; Peneva, Kalina; Gräfe, Stefanie; Kupfer, Stephan; Dietzek-Ivansic, Benjamin; Weigand, Wolfgang (European Journal of Inorganic Chemistry, 2022)
[FeFe] hydrogenase mimicking complexes containing N-substituted naphthalene monoimide (NMI) of peri-substituted dichalcogenides as bridging ligands have been prepared and characterized using different spectroscopic as well as by X-ray diffraction methods. The redox behaviour has been investigated by cyclic voltammetry, IR and UV-Vis spectroelectrochemistry (IR and UV-Vis SEC), electron paramagnetic resonance (EPR) spectroscopy and quantum chemical simulations. IR SEC and EPR experiments combined with DFT calculations revealed the non-innocent character of the NMI bridging ligands. EPR spectroscopy was applied to study the singly and doubly reduced state. Chemical reduction with one equivalent of Cp*2Co revealed the formation of an organic radical with a g-value of 2.0028 at room temperature. When two equivalents of Cp*2Co were used to carry out the second reduction, no EPR signal could be detected anymore. IR SEC measurements indicate the formation of an EPR-silent dimeric structure after the second reduction.
CRIS-Team Scopus Importer:2023-04-20